2021
DOI: 10.1083/jcb.202001042
|View full text |Cite
|
Sign up to set email alerts
|

An asymmetric junctional mechanoresponse coordinates mitotic rounding with epithelial integrity

Abstract: Epithelia are continuously self-renewed, but how epithelial integrity is maintained during the morphological changes that cells undergo in mitosis is not well understood. Here, we show that as epithelial cells round up when they enter mitosis, they exert tensile forces on neighboring cells. We find that mitotic cell–cell junctions withstand these tensile forces through the mechanosensitive recruitment of the actin-binding protein vinculin to cadherin-based adhesions. Surprisingly, vinculin that is recruited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…We also provide direct evidence that large epithelial rupture can arise by intercellular detachment during cell division, which provides a weak spot primed for disruption upon increased mechanical stress. This is consistent with previous observations that reinforcement of junctional attachment to the cytoskeleton prevents detachment during cell division in the Drosophila embryonic epithelium and mammalian cell culture [68, 69]. Dividing cells do not generate gaps upon aPKC inactivation in a mosaic tissue, showing that a direct effect in mitotic cells is not responsible for gap formation by itself.…”
Section: Discussionsupporting
confidence: 92%
“…We also provide direct evidence that large epithelial rupture can arise by intercellular detachment during cell division, which provides a weak spot primed for disruption upon increased mechanical stress. This is consistent with previous observations that reinforcement of junctional attachment to the cytoskeleton prevents detachment during cell division in the Drosophila embryonic epithelium and mammalian cell culture [68, 69]. Dividing cells do not generate gaps upon aPKC inactivation in a mosaic tissue, showing that a direct effect in mitotic cells is not responsible for gap formation by itself.…”
Section: Discussionsupporting
confidence: 92%
“…The area ( A ) and the perimeter ( P ) of the cell were measured in Fiji ImageJ, and the circularity ( C ) was calculated using the following equation: C = 4π × A / P 2 (ref. 76 ). At least ten cells of each cell line were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work in cell culture models showed that vinculin can be recruited asymmetrically in a force-dependent manner at sites of cadherin adhesion near mitotic cells. Whilst in this case, asymmetric recruitment promotes cell shape changes during cell division and maintenance of epithelial integrity (Monster et al, 2021), our study reveals that asymmetric vinculin requirements at cell junctions can also regulate cell fate decisions and tissue composition in the intestine. Our findings place vinculin in a feedback loop that couples the process of enterocyte differentiation to stem cell proliferation in the intestine.…”
Section: Discussionmentioning
confidence: 86%